2019
DOI: 10.3389/fpsyg.2019.01900
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Summer Intervention Drives Linear Growth of Reading Skill in Struggling Readers

Abstract: A major achievement of reading research has been the development of effective intervention programs for struggling readers. Most intervention studies employ a pre-post design, to examine efficacy, but this precludes the study of growth curves over the course of the intervention program. Determining the time-course of improvement is essential for cost-effective, evidence-based decisions on the optimal intervention dosage. The goal of this study was to analyze reading growth curves during an intensive summer int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…For example, as discussed by Ozernov-Palcik et al 14 , reading outcomes in children with developmental dyslexia may be substantially improved if we manage to anticipate difficulties through early screening and provide treatment during the most effective intervention window, i.e., at the very start of reading acquisition rather than after years of reading failure, which is current clinical practice. Although individual differences in the progression of structural-functional brain development may lead to variability in the precise timing of this window 15 , intervention-induced reading gains tend to be optimal for intervention between kindergarten and grade 2, after which these gains tend to stabilize 16 18 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, as discussed by Ozernov-Palcik et al 14 , reading outcomes in children with developmental dyslexia may be substantially improved if we manage to anticipate difficulties through early screening and provide treatment during the most effective intervention window, i.e., at the very start of reading acquisition rather than after years of reading failure, which is current clinical practice. Although individual differences in the progression of structural-functional brain development may lead to variability in the precise timing of this window 15 , intervention-induced reading gains tend to be optimal for intervention between kindergarten and grade 2, after which these gains tend to stabilize 16 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Also concerning was that only 17% of African American students were in the proficient group, compared with 46% of White students, 25% of Hispanic students, and 49% of Asian students. Recent reports of intensive summer reading intervention for children with reading disabilities have indicated improvements in word and pseudoword reading, symbol imagery, and oral reading fluency in a cohort of 6–9‐year olds 23 and decoding, oral reading skills, and comprehension in 6–12‐year olds 24 …”
Section: Discussionmentioning
confidence: 99%
“…Research from related fields is promising in this respect. Donnelly, Huber, and Yeatman (2019) showed that for so-called "struggling" readers there was a clear dose-response relationship, with a linear increase in reading ability as a function of reading intervention intensity.…”
Section: Discussionmentioning
confidence: 99%